Quercetin as a radiosensitizer for enhanced efficacy of radiotherapy in MCF-7 breast cancer cells - Mohammad Banparvar; Hamid Saeidi Saedi; Mona Haddad Zahmatkesh (Journal of Current Oncology and Medical Sciences)
Introduction: Radiation therapy is a primary approach for treating cancer. Utilizing natural radiosensitizer compounds is crucial to enhance radiosensitivity in tumor tissue while minimizing damage to normal tissue. This study aims to assess the impact of quercetin as a radiosensitizing compound in MCF-7 cells.